2013
DOI: 10.1152/ajpheart.00311.2013
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress modulates VCAM-1 expression in response to TNF-α and dietary lipids via interferon regulatory factor-1 in cultured endothelium

Abstract: DeVerse JS, Sandhu AS, Mendoza N, Edwards CM, Sun C, Simon SI, Passerini AG. Shear stress modulates VCAM-1 expression in response to TNF-␣ and dietary lipids via interferon regulatory factor-1 in cultured endothelium. Am J Physiol Heart Circ Physiol 305: H1149-H1157, 2013. First published August 9, 2013; doi:10.1152/ajpheart.00311.2013.-Dyslipidemia is a primary risk factor for cardiovascular disease, but the specific mechanisms that determine the localization of atherosclerotic plaques in arteries are not wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 46 publications
4
44
0
1
Order By: Relevance
“…Similar findings were observed by Dagia et al [30] who found that TNF-α activation of endothelial cells results in IRF-1-mediated VCAM-1 expression through binding of IRF-1 to the VCAM-1 promotor. Similarly, DeVerse et al [31] showed that in cultured endothelial cells, fluid shear stress signaling, synergistic with postprandial triglyceride-rich lipoproteins, transcriptionally augments cytokine-induced VCAM-1 expression in an IRF-1-dependent manner. In addition, Warfel and Agnillo [32] reported that anthrax lethal toxin enhanced nuclear expression of endothelial IRF-1 and induced VCAM-1 expression.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar findings were observed by Dagia et al [30] who found that TNF-α activation of endothelial cells results in IRF-1-mediated VCAM-1 expression through binding of IRF-1 to the VCAM-1 promotor. Similarly, DeVerse et al [31] showed that in cultured endothelial cells, fluid shear stress signaling, synergistic with postprandial triglyceride-rich lipoproteins, transcriptionally augments cytokine-induced VCAM-1 expression in an IRF-1-dependent manner. In addition, Warfel and Agnillo [32] reported that anthrax lethal toxin enhanced nuclear expression of endothelial IRF-1 and induced VCAM-1 expression.…”
Section: Discussionmentioning
confidence: 92%
“…Both this latter study and our study were performed under static conditions. Previous studies found monocyte adhesion to TNF-α-treated endothelium to be regulated by IRF-1-mediated VCAM-1 induction under flow conditions [20,30,31] . In patients with septic shock, increased endothelial permeability and vasodilation result in a dramatic drop in blood flow rate in certain microvascular compartments such as the capillaries [6,7,9] .…”
Section: Discussionmentioning
confidence: 92%
“…Shear stress not only stimulates endothelium-dependent dilation but is also a required signal for sustaining an anti-atherogenic vascular cell phenotype. Indeed, the role of shear stress in maintaining vascular health is supported by endothelial cell culture models (Mohan et al , 2003a; Mohan et al , 2003b; DeVerse et al , 2013; Ishibazawa et al , 2013), studies in perfused isolated arteries (Yamawaki et al , 2003; Woodman et al , 2005; Gambillara et al , 2006; Padilla et al , 2014), in vivo animal experiments (Korshunov & Berk, 2003; Nam et al , 2009; Wang et al , 2011; Loyer et al , 2014), and studies in human subjects (Thijssen et al , 2009; Tinken et al , 2009; Ishibazawa et al , 2013; Jenkins et al , 2013; Johnson et al , 2013). For example, Woodman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Hydrodynamic experiments were performed on HAEC monolayers using a microfluidic flow chamber device based on Hele-Shaw stagnation flow theory (14,46). The device induces a linearly decreasing WSS profile along the center line of the longitudinal axis for a given flow rate when vacuum adhered to a cell monolayer, facilitating the study of a wide range in WSS magnitudes within a single cell monolayer, while preserving information related to the spatial heterogeneity of response.…”
Section: Methodsmentioning
confidence: 99%